Leadership, Environment, and Lecturer Performance: The Mediating Role of Job Satisfaction in Islamic Higher Education - Samsul Rizal; Ismail Rasulong; Sentot Imam Wahjono (JURNAL AL-TANZIM, 2024)
Job satisfaction is a crucial factor in an organization's continuity and success, especially in higher education institutions, where retaining and motivating high-performing lecturers is essential for long-term success. This study explores the role of job satisfaction as a connecting factor between leadership behavior, academic atmosphere, and lecturer performance. The method used is an exploratory study with a sample of 200 permanent lecturers with at least a lecturer status from Islamic higher education institutions in South Sulawesi. Data were collected through an online survey using a Likert scale questionnaire, and data analysis was carried out using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The study results indicate that job satisfaction functions as a full mediating variable, where the impact of leadership behavior and academic atmosphere on lecturer performance is only significant through job satisfaction as a mediator. However, neither leadership behavior nor academic atmosphere substantially directly impacts lecturer performance. The implications of this study indicate the importance of job satisfaction in improving lecturer performance and the need for further research with a broader sample and more diverse variables to deepen understanding of the field of human resource management in the academic context.